Neutralizing monoclonal antibodies for early treatment of hospital‐acquired SARS‐CoV‐2 infection in hematologic patients. Issue 4 (2nd September 2022) - Bussini, Linda; Testi, Diletta; Tazza, Beatrice; Oltolini, Chiara; Mastaglio, Sara; Sepulcri, Chiara; Campoli, Caterina; Trapani, Filippo; Pasquini, Zeno; Zappulo, Emanuela; Bassetti, Matteo; Viale, Pierluigi; et al.
Abstract: Efficacy of early treatment with anti‐SARS‐CoV‐2 spike protein monoclonal antibodies (mAbs) for nosocomial SARS‐CoV‐2 infection in hematologic patients is unknown. Retrospective, cohort study conducted in four Italian teaching hospitals. We included adult patients with hematologic malignancies and hospital‐acquired SARS‐CoV‐2 infection diagnosed between November 2020 and December 2021. The principal exposure variable was administration of mAbs. The primary endpoint was clinical failure dea composite outcome of mortality and/or invasive and noninvasive ventilation within 90 days from infection onset. We included 52 patients with hospital‐acquired SARS‐CoV‐2 infection. Males were 29 (60%), median age was 62 (interquartile range [IQR] 48–70). Forty‐five (86%) patients were on chemotherapy or had received chemotherapy within 30 days. MAbs were administered in 19/52 (36%) patients. Clinical failure occurred in 22 (42%) patients; 21% (4/19) in mAbs group versus 54% (18/33) in non‐mAbs group ( p = 0.03). Other predictors of clinical failure were older age (median [IQR] 69 [61–72] versus 58 [46–66], p = 0.001), and higher Charlson comorbidity index (median [IQR], 5 [3.25‐5] versus 3 [2–5], p = 0.002). At multivariable Cox regression model, mAbs were independently associated with a significantly lower rate of clinical failure (HR 0.11, 95% CI 0.01–0.85, p = 0.01), after adjusting for confounders. In conclusion, mAbs are promising for early treatment of hematologic patients with healthcare‐related SARS‐CoV‐2 infection.